Service Quality Improvement of Calibration Laboratory by Integration of SERVQUAL and Kano’s Model into QFD - วิตรสุขุมาลย์, อนุภาพ; คุปตัษเฐียร, ณฐา (Frontiers in Engineering Innovation Research, 2015)
The objective of this research is to measure calibration service’s satisfactions and to plan for improving the calibration laboratory service to present for organization administrator using quality management tools. SERVQUAL and Kano’s Model. Quality levels are integrated and used as input to Quality Function Deployment (QFD). which is a structured approach to define customer needs and translate them into specific plans. Collection of 54 samples are showed that service users as satisfactions due to SERVQUAL. After calibration the instrument is in good condition as before and calibration report is accurate and complete. It’s must-be quality attributes from Kano's Model. The value from integrated model are into QFD phase 1 to acknowledge that “knowledge of calibration fields” These are importance technical requirements and enthusiastic service and put into QFD Phase 2 is to acknowledge that training efficacy and development of knowledge and skills.